MENGGALI POTENSI SISWA UNTUK MENENTUKAN PILIHAN PROGRAM STUDI DI PERGURUAN TINGGI - Handoyo, Sarwo Edy; Setijaningsih, Herlin Tundjung; Masman, Ronnie Resdianto; Puspitowati, Ida (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
The success of college graduates in a career is determined by the accuracy in choosing studies in college. Determination of study programs in college will be made by high school graduates when continuing their studies in college. Third grade high school students need to have adequate knowledge and information about the higher education system and their potential through brain color test before deciding to choose a college and study program. The PKM activity was carried out to equip 3rd grade students of SMAN 78 West Jakarta in the 2015/2016 academic year as partners. From the PKM activities carried out, partners are more interested in operational knowledge and information about universities, faculties, departments, study programs, accreditation, campus activities, tuition fees, scholarships, and graduate careers. The brain color of students is quite evenly distributed between students with type A (yellow), B (green), C (blue), and D (orange). Without classifying students based on their majors or gender, it turns out that the highest mind color is for type A (yellow) and the lowest is type D (orange), although the difference is not too large. However, there is a difference in the most types of mind color between science and social studies students. For science students, more are type A (yellow), while social studies students are type B (green). Male students' mind color is more type C (blue), while female students are type A (yellow).